2017
DOI: 10.1111/imb.12347
|View full text |Cite
|
Sign up to set email alerts
|

The multidimensional ionotropic receptors of Drosophila melanogaster

Abstract: Ionotropic receptors (IRs), which form ion channels, can be categorized into conserved 'antennal IRs', which define the first olfactory receptor family of insects, and species-specific 'divergent IRs', which are expressed in gustatory receptor neurones. These receptors are located primarily in cell bodies and dendrites, and are highly enriched in the tips of the dendritic terminals that convey sensory information to higher brain centres. Antennal IRs play important roles in odour and thermosensation, whereas d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
99
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(102 citation statements)
references
References 58 publications
(121 reference statements)
3
99
0
Order By: Relevance
“…Interestingly, many of the strongly connected food related PNs (VC5,VL2a, VL2p, VM1) receive sensory information via the family of ionotropic IR receptors [56]. These mainly respond to acids and polyamines [57]. The latter have been shown to be attractive in a T-maze but aversive in an egg-laying context (although this may involve the gustatory system) [58].…”
Section: Convergence Of Aversive Pn Channelsmentioning
confidence: 99%
“…Interestingly, many of the strongly connected food related PNs (VC5,VL2a, VL2p, VM1) receive sensory information via the family of ionotropic IR receptors [56]. These mainly respond to acids and polyamines [57]. The latter have been shown to be attractive in a T-maze but aversive in an egg-laying context (although this may involve the gustatory system) [58].…”
Section: Convergence Of Aversive Pn Channelsmentioning
confidence: 99%
“…In contrast, Missbach et al (2014) 82 could not find ORs or Orco relatives in their bristletail transcriptome, instead finding only 83 members of the ionotropic receptor (IR) gene family. Given evidence that IRs serve 84 olfactory roles in terrestrial crustaceans and insects (Rytz et al, 2013;Groh-Lunow et al, 85 2015;Rimal and Lee, 2018), they argued that olfaction in early-branching terrestrial 86 hexapods and apterygote insects is entirely IR-dependent, with Orco evolving as ancestral 87 OR from the GR lineage between the Archaeognatha and Zygentoma. Based on these 88 findings, Missbach et al (2014) suggested that the Orco/OR system evolved together 89 with flight in pterygote insects and left off with the observation that "the existence of 90 three Orco types remains mysterious".…”
mentioning
confidence: 99%
“…Despite the recent increase in knowledge about the main receptor families in olfaction in Drosophila (see reviews by Wilson, 2013; Carraher et al, 2015; Joseph and Carlson, 2015; Fleischer et al, 2018; Rimal and Lee, 2018), there are still many open questions that remain to be answered.…”
Section: Discussion and Closing Remarksmentioning
confidence: 99%
“…Furthermore, in both types of organisms, each OSN expresses one or very few olfactory molecular receptors, and the axons of OSNs that express the same receptor project to the same glomeruli in both the olfactory bulb and the antennal lobe (Su et al, 2009). These similarities and the fact that Drosophila is a widespread model organism in genetics and neurobiological research made its olfactory system an attractive and simple model to study olfaction (see, for example, the recent reviews by Wilson, 2013; Barish and Volkan, 2015; Carraher et al, 2015; Joseph and Carlson, 2015; Fleischer et al, 2018; Grabe and Sachse, 2018; Rimal and Lee, 2018). …”
Section: Introductionmentioning
confidence: 99%